Physical Activity, Social Support, and Mood in Older Adults during the COVID-19 Pandemic. (17th December 2021) - Inman, Morgan; Murphy, Clare; Strong, Jessica
Abstract: Research shows that increased physical activity is associated with improved mood and reduced symptoms of depression in older adults. Prior research has also found that loneliness and social isolation have a significant impact on the mental and physical well-being of older adults, with higher amounts of social connectedness and social activity associated with more frequent positive mood states. Overall social isolation is increased due to the COVID-19 pandemic and this could have a large impact on the physical and mental health of older adults. A group of 36 community dwelling older adults (Mean age = 70.5) completed questionnaires measuring physical activity, social activity, and social support, during the COVID-19 pandemic. Analyses found that perceived social support and average social network size significantly predicted positive mood states (F(2, 33)=3.32, p<0.05) accounting for 16.7% of the variance, with a large effect. After adding average number of hours of sedentary activity the model was not significant. Perceived social support was more predictive of positive mood (β=0.32) compared to network size (β=0.17). There was a trend for the same three variables to predict negative mood (F(3, 32)=2.76, p=0.06) accounting for 22% of the variance. Sedentary behaviour was the most predictive (t=2.68, p<0.05, β= 0.49). This suggests that perceived social support is most predictive of positive mood, and sedentary behaviour is predictive of negative mood during the COVID-19 pandemic.